2003
DOI: 10.4133/jeeg8.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Application of FM-CW and Pulse Radar

Abstract: Ground-penetrating radar (GPR) technology has supplied vital assistance in criminal investigations. However, law enforcement personnel desire further developments such that the technology is rapidly deployable, and that it provides both a simple user interface and sophisticated target identification. To assist in the development of target identification algorithms, our efforts involve gathering background GPR data for the various site conditions and circumstances that often typify clandestine burials. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…The advantages of using geophysical methods are the preservation of the crime scene, minimized destruction of forensic evidence, and a consequent possibility of reconstructing events at the scene [2][3][4][5]. These methods, particularly ground-penetrating radar (GPR), are non-intrusive techniques that allow for the survey of extensive areas so that recover buried remains and clandestine burial caves can be located and recovered [6,7]. GPR is a relatively quick technique that gives an overall qualitative internal image and can provide high penetration depth depending on the soil nature and the chosen frequency for screening [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of using geophysical methods are the preservation of the crime scene, minimized destruction of forensic evidence, and a consequent possibility of reconstructing events at the scene [2][3][4][5]. These methods, particularly ground-penetrating radar (GPR), are non-intrusive techniques that allow for the survey of extensive areas so that recover buried remains and clandestine burial caves can be located and recovered [6,7]. GPR is a relatively quick technique that gives an overall qualitative internal image and can provide high penetration depth depending on the soil nature and the chosen frequency for screening [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have noted that field soil properties greatly influence the appropriate transmission of the radar wave. The presence of conductive media, such as clay-rich subsoil, can attenuate the electromagnetic signal, and detecting underground features becomes difficult because the signal is not able to penetrate [7,11,12]. The use of GPR in forensic applications is a quite recently implemented practice, as it has only been used since the 1990s [13], but in recent years, the amount of published works with successful results in this context has increased [3][4][5]11,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Forensic anthropology includes the study of war crime and homicide victims, as well as mass disasters. Since the 1980s, GPR has been successfully applied to assist in forensic investigations, and interesting information can be provided about the dimensions and limits of graves, as well as to detect buried bodies or bone remains (Freeland et al 2003;Schultz and Martin 2011). These results allow saving time-consuming and efforts since smaller areas are highlighted for further testing with traditional searching methods such as excavations.…”
mentioning
confidence: 95%
“…The central frequencies of 225, 450 and 900 MHz were evaluated in this work, and the GPR data showed 450 MHz frequency antenna to be optimal for burial target detection. Other authors, as Freeland et al (2003), analysed the capabilities of the 400 and 900 MHz to assist in criminal investigations. They concluded that 400 MHz was appropriate to produce detailed data, discerning the grave walls and folded tarp covering the lower body.…”
Section: Human Remains and Life Detectionmentioning
confidence: 99%
See 1 more Smart Citation